2006
DOI: 10.1182/blood-2005-09-3716
|View full text |Cite
|
Sign up to set email alerts
|

Suicide gene therapy of graft-versus-host disease induced by central memory human T lymphocytes

Abstract: In allogeneic hematopoietic cell transplantation (allo-HCT), the immune recognition of host antigens by donor T lymphocytes leads to a beneficial graft-versus-leukemia (GvL) effect as well as to life-threatening graft-versus-host disease (GvHD). Genetic modification of T lymphocytes with a retroviral vector (RV) expressing the herpes simplex virus-thymidine kinase (TK) suicide gene confers selective sensitivity to the prodrug ganciclovir (GCV). In patients, the infusion of TK ؉ lymphocytes and the subsequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 58 publications
(76 reference statements)
3
64
1
Order By: Relevance
“…injection of 12-day CD3/CD28 bead activated huT into anti-CD122 treated and irradiated NOD/SCID recipients (58% lethal X-GVHD for 12-day activated huT versus 100% for non-activated huT). In summary, our findings further illustrate the preservation of huT cell function following CD3/ CD28 bead stimulation and will allow us to evaluate the efficacy of GVHD prevention strategies, such as suicide gene therapy [39], requiring ex vivo T cell activation and expansion.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…injection of 12-day CD3/CD28 bead activated huT into anti-CD122 treated and irradiated NOD/SCID recipients (58% lethal X-GVHD for 12-day activated huT versus 100% for non-activated huT). In summary, our findings further illustrate the preservation of huT cell function following CD3/ CD28 bead stimulation and will allow us to evaluate the efficacy of GVHD prevention strategies, such as suicide gene therapy [39], requiring ex vivo T cell activation and expansion.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, although the X-GVHDinducing potential of 4-and 8-day activated huT cells were similar, we found that the engraftment, in-vivo expansion, and tissue infiltration of 8-day activated huT cells was significantly decreased compared to cells that were cultured for only 4 days. This decreased huT cell engraftment and expansion following prolonged ex-vivo activation may explain why Bondaza et al [39] observed decreased lethal X-GVHD following the i.p. injection of 12-day CD3/CD28 bead activated huT into anti-CD122 treated and irradiated NOD/SCID recipients (58% lethal X-GVHD for 12-day activated huT versus 100% for non-activated huT).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…15 In humans, it has been shown that CD4 þ CD62L þ T cells responded better to alloantigens than the CD62L neg memory subsets in both proliferation and cytotoxicity assays, 16 and in vitro-generated T CM appeared to be more potent than T EM in an experimental model of GVHD. 17 Thus, the initiation of GVHD seems to depend on the representation of alloreactive cells within naive and/or central memory subsets in the graft, but no clinical study has yet sustained these experimental or in vitro data.…”
Section: Introductionmentioning
confidence: 99%
“…Several phase-I/II studies using this technology have been completed and thus provide proof of principle. 15,16 …”
Section: Manipulation Of T Lymphocytesmentioning
confidence: 99%